1st of all, if you mean 9-y2 its simply a difference between two squares formula (3-y) (3+y)
Chat with our AI personalities
x2 - y2 + 9x - 9y =(x2 + 9x) - (y2 + 9y) =x(x + 9) - y(y + 9)================================Another way to go after it:x2 - y2 + 9x - 9y =(x2 - y2) + 9x - 9y =(x + y) (x - y) + 9 (x - y) =(x + y + 9) (x - y)
(x - y)2 = x2 - 2xy + y2
7(3y-2)-(-4y+9)
y² - y all depends on the value of y. If you want to factor the expression, then we have y(y - 1)
y^3 + y^2 - 6 (y+2) (y-3) i think